Lipid Peroxidation in Subretinal Fluid: Some Light on the Prognosis Factors - Bosch-Morell, Francisco (Biomolecules, 2021)
The aim of this study was to identify a relation between the clinical characteristics and differences in lipid peroxidation in the subretinal fluid (SRF) of rhegmatogenous retinal detached patients by malondialdehyde (MDA) quantification. We collected 65 SRF samples from consecutive patients during scleral buckling surgery in rhegmatogenous retinal detachment (RRD) eyes. In addition to a complete ophthalmic evaluation, we studied the refractive status, evolution time, and the number of detached retinal quadrants to establish the extension of RRD. We studied the clinical aspects and oxidative stress and compared the characteristics among groups. We found that neither the evolution time of RRD nor the patients’ age correlated with the MDA concentration in the SRF. The MDA and the protein content of the SRF increased in the patients with high myopia and with more extended RRD. Our results suggest that oxidative imbalance was important in more extended retinal detachment (RD) and in myopic eyes and should be taken into account in the managing of these cases.